Long Term Standard Analysis of Steam Shower Therapy and Health Care for Postpartum Mother - Br Sinuhaji, Lidya Natalia; Triana Ginting, Siska Suci; Seriati, Tetti (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Background: According to the 2015 Indonesian Demographic Health Survey (IDHS), age in childbirth is large enough to target the Maternal Mortality Rate (MMR). This page looks at 228 / 100,000 KH modes as much as 28% of bleeding, 24% of eclampsia, 11% of infections and 26, 3% of AKI that occur during childbirth. From my previous research, more benefits of Steam Shower is can be used for postpartum mothers, removing toxins in the body, normalizing blood circulation, burning calories, improving stamina, freshness of the body, cleansing dirty blood. The purpose of this study was to find out the standard time for process Steam Shower to help for postpartum maternal health. The research method is descriptive, which is qualitative with an interpretive paradigm with ethical and ethnic approaches. This research is data-based naturalistic to see phenomena naturally. The results of processing of this study are noted that mothers will feel the benefits are sufficient within 15-20 minutes. According to informants within 15-20 minutes the steam produced from 21 kinds of spices can still be felt by the aroma of the Steam Shower therapy, but there are still mothers who do less than 15 minutes with the reason of not being able to. It does not matter whether it is necessary to inform the duration of Steam Shower therapy that is useful for health care for postpartum mothers. Suggestions for research results can be used as material for knowledge and information for health workers such as midwives in providing midwifery care without neglecting cultural aspects.